Bioimpedancemetry for the assessment of periodontal tissue inflammation: a numerical feasibility study. Issue 6 (26th April 2017) - Cosoli, Gloria; Scalise, Lorenzo; Cerri, Graziano; Russo, Paola; Tricarico, Gerardo; Tomasini, Enrico Primo
Abstract: In dentistry possible inflammatory episodes of oral cavity can be very frequent (periodontitis, mucositis, peri-implantitis) and they can have serious consequences. Indeed, peri-implantitis is still the principal cause of implant failure. Impedance values of biological tissues are related to the physiological/pathological state of the tissue itself. In fact, an inflamed site exhibits an impedance value lower than that of the corresponding healthy tissue. Based on these observations, the aim of this work is to determine if impedancemetric measurements are able to provide information about the inflammatory state of tissues. A numerical 3D model has been realized to simulate the measurement conditions present in the event of inflammation around a dental implant. The aim is to understand if it is possible to determine the presence of an inflamed tissue and to locate its site, so that the treatment could be specifically focused in that specific area. A simplified geometry reproducing the implant has been realized in order to validate the numerical model by means of experimental measurements. The obtained results are satisfactorily accurate, so the model can be considered reliable. Therefore, multiple simulations have been run on the original model to carry out a parametric study in terms of different conductivity values, different volumes of inflamed tissues and different measurement frequencies. The advantages and limits of such a method have been shown to properly define the main constraints for the system design.